Plasma transfusion in the intensive care unit - van Haeren, Maite M T; Raasveld, Senta Jorinde; de Bruin, Sanne; Reuland, Merijn C; van den Oord, Claudia; Schenk, Jimmy; Aubron, Cécile; Bakker, Jan; Cecconi, Maurizio; Feldheiser, Aarne; de Grooth, Harm-Jan; Meier, Jens; et al. (Transfusion, 2025)
BACKGROUND: Current guidelines discourage prophylactic plasma use in non-bleeding patients. This study assesses global plasma transfusion practices in the intensive care unit (ICU) and their alignment with current guidelines. STUDY DESIGN AND METHODS: This was a sub-study of an international, prospective, observational cohort. Primary outcomes were in-ICU occurrence rate of plasma transfusion, proportion of plasma events of total blood products events, and number of plasma units per event. Secondary outcomes included transfusion indications, INR/PT, and proportion of events for non-bleeding indications. RESULTS: Of 3643 patients included, 356 patients (10%) experienced 547 plasma transfusion events, accounting for 18% of total transfusion events. A median of 2 (IQR 1, 2) units was given per event excluding massive transfusion protocol (MTP) and 3 (IQR 2, 6) when MTP was activated. MTP accounted for 39 (7%) of events. Indications of non-MTP events included active bleeding (54%), prophylactic (25%), and pre-procedure (12%). Target INR/PT was stated for 43% of transfusion events; pre-transfusion INR/PT or visco-elastic hemostatic assays (VHA) were reported for 73%. Thirty-seven percent of events were administered for non-bleeding indications, 54% with a pre-transfusion INR < 3.0 and 30% with an INR < 1.5. DISCUSSION: Plasma transfusions occurred in 10% of ICU patients. Over a third were given for non-bleeding indications and might have been avoidable. Target INR/PT was not stated in more than half of transfusions, and pre-transfusion INR/PT or VHA was not reported for 27%. Further research and education is needed to optimize guideline implementation and to identify appropriate indications for plasma transfusion.
Keywords: transfusion practices; transfusion; krevní plazma; převod jednotlivých krevních složek; Hemorrhage; critically ill; Humans; ICU; lidé středního věku; Female; Aged; senioři; lidé; Practice Guidelines as Topic; ženské pohlaví; Male; jednotky intenzivní péče; Middle Aged; Plasma; intensive care unit; směrnice pro lékařskou praxi jako téma; Blood Component Transfusion; krvácení; Intensive Care Units; mužské pohlaví; prospektivní studie; plasma; Prospective Studies